Micronutrient Intake in Pregnant Women and its Association with the Incidence of Low Birth Weight (LBW) - Dian Fitriyani; Sri Hazanah; Lina Darmayanti Bainuan; Yunita Kristina; Endah Sri Rahayu (Miracle Journal Get Press, 2025)
Low birth weight (LBW) remains a public health problem that contributes to high rates of neonatal morbidity and mortality. This study aimed to analyse the association between pregnant women's micronutrient intake and the incidence of LBW. The study design was a prospective cohort study involving 210 second to third trimester pregnant women in Padang City in 2025. Micronutrient intake was assessed using the 3x24 hour food recall method, while the baby's birth weight data was obtained during delivery. Chi-square test and logistic regression were used for analysis. The results showed the prevalence of LBW was 15.2%. Intake of iron, zinc, vitamin D, and folic acid were found to be significantly associated with LBW (p < 0.05), while vitamin A and vitamin B12 showed no significant association. Further analysis revealed that iron deficiency was the dominant factor contributing most to the incidence of LBW. These findings confirm the importance of micronutrient fulfilment during pregnancy, both through a nutritionally balanced diet and supplementation, to prevent LBW. Therefore, micronutrient interventions need to be prioritised in maternal and child health programmes, especially through strengthening nutrition counselling and monitoring supplement compliance in antenatal care services.